A collaborative approach to event-led regeneration: The governance of legacy from the 2014 Commonwealth Games. (December 2015) - Christie, Linda; Gibb, Kenneth
This paper stresses the role of collaborative working within the new urban governance literature. The legacy approach for the 2014 Commonwealth Games has thus far been well received as an example of successful partnership working. Glasgow's approach to legacy is discussed within the wider context of an increasing strategic focus on event-led regeneration. High-level political support for legacy led to the early development of Glasgow's Legacy Plan in 2009, followed by the development of a legacy partnership: the Glasgow Legacy Board . The paper contributes to the literature by exploring a conceptual understanding of inter-governmental working for regeneration, through close examination of Glasgow's legacy approach, development, structure and governance. To what extent does Glasgow's collaborative approach to legacy represent a new institutional form of network governance for the delivery of urban regeneration in Scotland? The paper also reflects on the long-term transferability of this collaborative approach to legacy for the delivery of urban regeneration in Scotland beyond 2014.